(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Multiple emulsions are complex polydispersed organizations where both oil-in-water and water-in-oil emulsion are present simultaneously, which are stabilized by lipophilic and hydrophilic surfactants, respectively. To achieve stable multiple emulsions, the proportion of these surfactants is critical. Between the two types of multiple emulsions, water-in-oil-in-water (W/O/W) and oil-in-water-in-oil, the former has a wider range of applications and is thus investigated in more depth. Multiple emulsion development, preparation procedures, and in vitro evaluation methodologies have all been updated. Numerous elements impacting the stability of multiple emulsions, as well as stabilization strategies, are explored in detail, with a focus on W/O/W type multiple emulsions. Multiple emulsions are a possible carrier because they have desirable drug release mechanisms and rates, as well as a favorable in vivo fate. It has a wide range of uses, including regulated, targeted distribution, flavor masking, bioavailability augmentation, enzyme immobilization, and so on. In the microencapsulation process, several emulsions have also been regarded an intermediate phase. They are the systems of increasing interest for the oral delivery of hydrophilic drugs, which are unbalanced in the gastrointestinal tract such as proteins and peptides. It will provide a novel carrier system for the administration of pharmaceuticals, cosmetics, and medicinal agents as procedures for preparation, stabilization, and rheological characterization of multiple emulsions advance. Formulation, stabilization procedures, and prospective uses of various emulsion systems are all considered in this assessment.